A survey of literature on automated storage and retrieval systems from 2009 to 2019. Issue 4 (3rd May 2023) - Bertolini, Massimo; Neroni, Mattia; Uckelmann, Dieter
This paper provides a literature review on automated storage and retrieval systems based on the Scopus database. The last comprehensive literature review that analyses the subject in its entirety dates back to 2009 by Roodbergen and Vis. Since then, the scientific community has provided many new efficient solutions, most of which are collected in Scopus. All these new published solutions need to be classified and summarised; thus, for this paper, more than one thousand scientific publications were analysed in order to classify the proposed solutions, deliver new academic insights to the field, and provide clear guidelines for researchers and practitioners.